Pemberian Rebusan Piper Crocatum dan Annona Muricata Linn dalam Penanganan Keputihan pada Remaja Putri - Febriyanti, Sylvia Sri; Apriyani, Magdalena Tri Putri; Sugesti, Retno (Jurnal Ilmu Kebidanan, 2024)
Background: According to statistical data, the population in Banten Province reached 11,358,740 people or 27.60% of women experienced vaginal discharge. Meanwhile, from data taken from SMPN 3 Cipeucang, there were around 56 female students who had experienced vaginal discharge ranging from vaginal discharge without complaints to those who had experienced vaginal discharge with complaints of itching. Vaginal discharge (Flour Albus) is fluid that comes out of the genitalia, not blood. Vaginal discharge is divided into 2, namely physiological vaginal discharge and pathological vaginal discharge. There are several treatments for vaginal discharge, one of which is using herbs. Several studies have shown results that there is a decrease in the consistency of vaginal discharge and even cure of vaginal discharge by administering piper crocatum decoction and Annona muricata linn decoction. Methods: ; Case Study, namely a series of activities relating to Library data collection methods. Results: The results of midwifery care for respondent 1 who was given the piper crocatum decoction intervention showed the effect of reducing vaginal discharge and even curing vaginal discharge on day 5. Meanwhile for respondent 2 who was given the Annona muritaca linn decoction intervention there was an effect of reducing vaginal discharge on day 4 with healing time on day 8. Conclusion There is an influence on giving piper crocatum decoction and Annona muricata linn decoction in treating vaginal discharge in young women even though there is a difference in days in the healing process.